The relative contribution of the decreasing trend in tumour thickness to the 2010s increase in net survival from cutaneous malignant melanoma in Italy: a population‐based investigation. (31st May 2022) - Zamagni, Federica; Bucchi, Lauro; Mancini, Silvia; Crocetti, Emanuele; Dal Maso, Luigino; Ferretti, Stefano; Biggeri, Annibale; Villani, Simona; Baldacchini, Flavia; Giuliani, Orietta; Ravaioli, Alessandra; Vattiato, Rosa; et al.
Abstract: Background: The long‐term increase in survival from cutaneous malignant melanoma (CMM) is generally attributed to the decreasing trend in tumour thickness, the single most important prognostic factor. Objectives: To determine the relative contribution of decreased tumour thickness to the favourable trend in survival from CMM in Italy. Methods: Eleven local cancer registries covering a population of 8 056 608 (13.4% of the Italian population in 2010) provided records for people with primary CMM registered between 2003 and 2017. Age‐standardized 5‐year net survival was calculated. Multivariate analysis of 5‐year net survival was undertaken by calculating the relative excess risk (RER) of death. The relative contribution of the decrease in tumour thickness to the RER of death was evaluated using a forward stepwise flexible parametric survival model including the available prognostic factors. Results: Over the study period, tumour thickness was inversely associated with 5‐year net survival and multivariate RER in both sexes. The median thickness was 0.90 mm in 2003–2007, 0.85 mm in 2008–2012 and 0.75 mm in 2013–2017 among male patients, and 0.78 mm, 0.77 mm and 0.68 mm among female patients, respectively. The 5‐year net survival was 86.8%, 89.2% and 93.2% in male patients, and 91.4%, 92.0% and 93.4% in female patients, respectively. In 2013–2017, male patients exhibited the same survival as female patients despite having thicker lesions. For them, the increasing survival trend was more pronounced with increasing thickness, and the inclusion of thickness in the forward stepwise model made the RER in 2013–2017 vs. 2003–2007 increase from 0.64 [95% confidence interval (CI) 0.51–0.80] to 0.70 (95% CI 0.57–0.86). This indicates that the thickness trend accounted for less than 20% of the survival increase. For female patients, the results were not significant but, with multiple imputation of missing thickness values, the RER rose from 0.74 (95% CI 0.58–0.93) to 0.82 (95% CI 0.66–1.02) in 2013–2017. Conclusions: For male patients in particular, decrease in tumour thickness accounted for a small part of the improvement in survival observed in 2013–2017. The introduction of targeted therapies and immune checkpoint inhibitors in 2013 is most likely to account for the remaining improvement. Abstract : What is already known about this topic? Long‐term increase in survival from cutaneous malignant melanoma (CMM) is generally attributed to the decreasing trend in tumour thickness, the single most important prognostic factor. Targeted therapies and immune checkpoint inhibitors, introduced during the past decade, were shown in phase III trials to improve the prognosis of patients with unresectable and metastatic CMM, but their contribution to the persistent upward trend in overall survival at the population level in Europe is ill‐defined. What does this study add? In Italy, the 5‐year net survival from CMM in 2013–2017 improved vs. 2003–2007, especially among male patients and in the two highest tumour thickness categories. Male patients, for the first time, exhibited the same survival as female patients despite having still thicker lesions. The decrease in median tumour thickness accounted for a small part of the improvement. Novel therapies, approved in 2013, are the factor most likely to account for the remaining improvement. In Italy, the 5‐year net survival from melanoma in 2013–2017 improved vs. 2003–2007, especially among male patients and in the two highest tumour thickness categories. Male patients, for the first time, exhibited the same survival as female patients despite having still thicker lesions. The decrease in median tumour thickness accounted for a small part of the improvement. Novel therapies, approved in 2013, are the factor most likely to account for the remaining improvement. Linked Comment: I.T. Harvima and R.J. Harvima. Br J Dermatol 2022; 187:6–7 . Plain language summary available online